Implantes pós-exodônticos: relato de caso - Gaetti-Jardim, Ellen Cristina [UNESP]; Aguiar, Carlos Roberto; Pereira, Cassiano Costa Silva [UNESP]; Ponzoni, Daniela [UNESP]; Aranega, Alessandra [UNESP]; Shinohara, Elio Hitoshio [UNESP]; Magro Filho, Osvaldo [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP] (My University, 2011)
With the search for treatments faster and aesthetic improvement of materials and surgical techniques, immediate implants have become a clinical reality increasingly practiced. Thus, based on literature the specific purpose of this study was to address critically the concepts of immediate implants, discussing issues related to dental extraction, milling technique, care of the periodontal tissues support and protection, prosthetic replacement, benefits, indications and contraindications. To this end, from Pubmed electronic crawler Medline, 54 articles published between 1990 and 2009, over 4 items classics, all in English were selected. The Studies have shown success rates for this technique Conventional techniques like two-stage surgery, many different techniques and planning are present among these techniques, and implants more immediate subject to failures.

Com a busca por tratamentos mais rápidos e estéticos, melhoria dos materiais e técnicas cirúrgicas, os implantes imediatos vêm se tornando uma realidade clínica cada vez mais praticada. Sendo assim, baseado na literatura específica o objetivo deste estudo foi abordar de modo crítico os conceitos dos implantes imediatos, discutindo aspectos relacionados à extração dental, técnica de fresagem, cuidados com os tecidos periodontais de suporte e proteção, reposição protética, vantagens, indicações e contra-indicações. Neste intuito, a partir do indexador eletrônico Pubmed Medline, 54 artigos publicados no período entre 1990 e 2009, mais 4 artigos clássicos, todos na língua inglesa foram selecionados. Os estudos mostraram taxas de sucesso para esta técnica semelhante às técnicas convencionais de dois estágios cirúrgicos, muitas diferenças técnicas e de planejamento estão presente entre estas técnicas, sendo os implantes imediatos mais sujeitos a falhas.
Implants post-extraction: case report
Keywords: Dental implants; Tooth extraction; Periodontics; Implantes dentários; Extração dentária; Periodontia